Implikasi Pengakuan Korporasi Sebagai Subjek Hukum Pidana Dalam KUHP Nasional: Kajian Aspek Konseptual Dan Normatif - Radhali; Asnawi, M. Iqbal (International Journal of Demos (IJD), 2025)
Abstract The increasingly complex business environment has positioned corporations as dominant actors in socio-economic life, while simultaneously posing potential negative impacts through corporate crime. This research aims to analyze the implications of recognizing corporations as criminal law subjects in the national Criminal Code, both from conceptual and normative aspects, and to formulate recommendations for developing an effective corporate criminal liability system. The research employs a normative juridical method with three approaches: statutory approach, conceptual approach, and comparative approach, supported by prescriptive-qualitative analysis of primary, secondary, and tertiary legal materials. The results indicate that the national Criminal Code has adopted a comprehensive juridical construction in regulating corporate criminal liability, encompassing parameters for determining corporate fault, attribution mechanisms based on a combination of identification theory, aggregation theory, and corporate culture theory, as well as sanctions design that integrates restorative justice approaches. The implementation of this system requires systematic regulatory harmonization and institutional capacity strengthening, including human resource competency development, supporting infrastructure, and knowledge management systems. The research concludes that recognizing corporations as criminal law subjects represents a progressive step that requires support through technical regulatory development, law enforcement capacity building, and effective inter-agency coordination mechanisms. Keywords: corporate criminal liability, national Criminal Code, restorative justice, corporate crime, regulatory harmonization   Abstrak Perkembangan dunia usaha yang semakin kompleks telah menempatkan korporasi sebagai aktor dominan dalam kehidupan sosial-ekonomi masyarakat, namun sekaligus berpotensi menimbulkan dampak negatif melalui kejahatan korporasi. Penelitian ini bertujuan menganalisis implikasi pengakuan korporasi sebagai subjek hukum pidana dalam KUHP nasional, baik dari aspek konseptual maupun normatif, serta merumuskan rekomendasi untuk pengembangan sistem pertanggungjawaban pidana korporasi yang efektif. Penelitian menggunakan metode yuridis normatif dengan tiga pendekatan: pendekatan perundang-undangan, pendekatan konseptual, dan pendekatan perbandingan, yang didukung analisis preskriptif-kualitatif terhadap bahan hukum primer, sekunder, dan tersier. Hasil penelitian menunjukkan bahwa KUHP nasional telah mengadopsi konstruksi yuridis yang komprehensif dalam mengatur pertanggungjawaban pidana korporasi, mencakup parameter penentuan kesalahan korporasi, mekanisme atribusi berdasarkan kombinasi identification theory, aggregation theory, dan corporate culture theory, serta desain sanksi yang mengintegrasikan pendekatan keadilan restoratif. Implementasi sistem ini membutuhkan harmonisasi regulasi yang sistematis dan penguatan kapasitas kelembagaan yang mencakup pengembangan kompetensi SDM, infrastruktur pendukung, dan sistem manajemen pengetahuan. Penelitian menyimpulkan bahwa pengakuan korporasi sebagai subjek hukum pidana merupakan langkah progresif yang memerlukan dukungan pengembangan regulasi teknis, penguatan kapasitas penegak hukum, dan mekanisme koordinasi antar lembaga yang efektif. Kata kunci: pertanggungjawaban pidana korporasi, KUHP nasional, keadilan restoratif, kejahatan korporasi, harmonisasi regulasi